Viral Infection Prevention and Control Precautions - Brajesh Hindal, Bharat Chouhan (International Journal of Pharmaceutical & Biological Archive, 2024)
This review article mainly focused on the prevention and control precautions of viral disease which continue to cause considerable the morbidity and the mortality around the world. Prevention included: Primary preventions such as vaccination, pre- and post-exposure prophylaxis, reduction of viral exposure, hygiene/disinfection, screening of blood products, raising awareness/counseling and secondary prevention such as treatment of infected people, identification and counseling of infected people, and diagnosis of infected people. In control and precautions included avoiding sexual contact with HIV-infected individuals, avoiding drug abuse, screening of blood before transfusion, using condoms during sexual contact, avoiding contaminated syringe and needles, wash hands as needed, and maintain personal hygiene.